Shramahara Mahakasya, a traditional polyherbal formulation, induces anti-anxiety activity in hippocampal neurons by effectuating SOD2-mediated protection against oxidative stress - Saakshi Saini; Viney Kumar; Swati Haldar; Samrat Chauhan; Pratibha Demiwal; Souvik Ghosh; Sumeet Gupta; Debabrata Sircar; Bidhan Mahajon; Partha Roy (Phytomedicine Plus)
Background: Shramahara Mahakasya (SM) is an Ayurvedic polyherbal formulation known for its anti-fatigue and anti-anxiety effects on the human body. However, its mechanism of action remains largely unexplored. In this study, we investigated the intricate mechanisms through which SM polyherbal extract exerts neuroprotective and anxiolytic effects in cultured HT-22 cells and rodent models. Method: In this study, the chemical composition of SM was first identified using gas chromatography-mass spectrometry (GC-MS) and liquid chromatography-mass spectrometry (LC-MS). The antioxidant potential of SM was evaluated through antioxidant assays such as DPPH, ABTS and FRAP. The neuroprotective activity of SM (200 and 600 μg/mL) was investigated in glutamate (10 mM) assaulted HT-22 cells. The anxiolytic activity of SM (50 and 100 mg/kg) was assessed in a caffeine (50 mg/kg) induced anxiety model of Sprague Dawley rats. The possible underlying mechanisms for the neuroprotective and anxiolytic activities of SM were explored through biochemical assays and brain histology. Results: Our findings suggest that SM has antioxidant and neuroprotective potential, as evidenced by a decrease in ROS accumulation, Ca2+ overload, mitochondrial membrane potential (MMP) loss, and apoptosis in HT-22 cells subjected to glutamate-induced oxidative stress. The extract also increased SOD2 levels and decreased cleaved caspase-3 levels across various treatment sets. The anxiolytic activity of SM was demonstrated by improved behavior of the animals in the elevated plus maze test and increased SOD activity in the brain. SM exhibited the most effective improvements in anxiety disorder at a dose of 100 mg/kg body weight in rats. Conclusions: This study is a pioneering investigation depicting the antioxidant, neuroprotective, anti-apoptotic, and anxiolytic potential of SM formulation against glutamate/caffeine-induced oxidative stress and anxiety in both in vitro and in vivo situations. Overall, our study suggests that the regular consumption of SM formulation could effectively prevent anxiety symptoms by reducing oxidative stress in neuronal cells.